157 Educational attainment of children born to mothers with MS. Issue 12 (14th November 2019) - Owen Pickrell, W; Lacey, Arron S; Harding, Katharine; Middleton, Rod; Tallantyre, Emma C; Ingram, Gillian; Pearson, Owen R; Rees, Mark I; Robertson, Neil P
Abstract : Introduction: Multiple sclerosis (MS) causes long-term disability with broad socioeconomic consequences. This may influence educational attainment in children of affected individuals. We investigated whether having a mother with MS affects performance in Welsh national attainment tests. Method: Anonymised lists of 1584 women with MS diagnosed in two neuroscience centres (Cardiff, Swansea) were linked to population level routinely-collected health and education data. We identified children born to mothers with MS and compared performance in Key Stage (KS) 2–4 tests, taken at ages 11, 14 and 16, to a control group (matched for deprivation score, maternal age, year of birth, gestational age and birth weight). We measured core subject indicator (CSI) as an outcome measure (proportion achieving minimum standard in core subjects). Results: 525 children from mothers with MS had test results available from 2003–2016; there were 2217 matched controls. There was no significant overall difference in CSI achievement between cases and controls: KS2 (85.3%v84.3%); KS3 (75%v71.5%); KS4 (52.1%v50.5%). Greater Expanded Disability Score Status did not significantly worsen performance but longer time since diagnosis improved performance in KS3 and KS4. Conclusion: Having a mother with MS did not significantly worsen performance in national attainment tests and was associated with improved performance in some subgroups.